1983
DOI: 10.1007/bf01411618
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer prior to fusion

Abstract: In reactions between very asymmetric projectile-target systems charge is preferably transferred from the lighter to the heavier nucleus. This leads to a decrease of the potential barrier between the nuclei and increase of the fusion cross-section. We perform trajectory calculations with energy dissipation and proton transfer to estimate the magnitude of the effect.Our theoretical understanding of heavy-ion induced fusion reactions has been substantially extended during the past few years. The simple model that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Hartmann and Gross [84] have shown that in asymmetric nuclear reactions, there is a charge transfer from the lighter to the heavier nucleus immediately 2.9 ± 1.6 Table 8.2: Capture cross sections for all experiments used in the systematic study of paired reactions, calculated by the method described in [29] with updated parameters [32]. Peak 1n cross sections and ratios for these values are included for comparison.…”
Section: Discussion Of Systematic Study Resultsmentioning
confidence: 99%
“…Hartmann and Gross [84] have shown that in asymmetric nuclear reactions, there is a charge transfer from the lighter to the heavier nucleus immediately 2.9 ± 1.6 Table 8.2: Capture cross sections for all experiments used in the systematic study of paired reactions, calculated by the method described in [29] with updated parameters [32]. Peak 1n cross sections and ratios for these values are included for comparison.…”
Section: Discussion Of Systematic Study Resultsmentioning
confidence: 99%
“…Although the neutron transfer for ' Mo and 3Nb has positive Q values, particularly for two-neutron pickup, the yields for proton transfer are not much less than the neutron transfer. It has been pointed out [28,29] that charge transfer with a negative Q value could also enhance fusion if the Q-matching conditions for transfer are valid. Furthermore, coupled-channel calculations show that multinucleon transfer plays an important role in the fusion enhancement [30].…”
Section: Experiments and Datamentioning
confidence: 99%